Pengaruh Metode Bercerita Berbasis Budaya Jambi Menggunakan Wayang Terhadap Perkembangan Sosial Emosional Anak Usia 5-6 Tahun Di TK IT Al-Azka Kota Jambi - Alifya Yuliani; Indryani; Nyimas Muzzomi (Advances In Education Journal, 2026)
Social-emotional skills are a child's ability to recognize, understand, and manage their own emotions while interacting positively with others. At an early age, this skill is crucial. Some children experience issues such as shyness in speaking in front of their peers, a lack of confidence in speaking and answering questions, impolite behavior, and difficulty controlling their emotions, often harassing their peers, and damaging their belongings. The purpose of this study was to determine the effect of Jambi culture-based storytelling using wayang puppets on the social-emotional development of 5-6-year-old children at Al-Azka Kindergarten in Jambi City. This research was an experimental study using a one-group pre-test-posttest design. The population was 49 children. Purposive sampling was used, selecting 14 children from class B3. Data collection techniques included observation and documentation. The research instrument used was an observation sheet in accordance with the observation guide. Data analysis techniques included normality tests and homogeneity tests, and hypothesis testing using the t-test. The results of the study showed that Thitung > Ttabel, namely 21,649 > 1,770, so H0 was rejected and Ha was accepted, so it can be concluded that there is an influence of the Jambi Culture-Based Storytelling Method Using Wayang on the Social Emotional Development of Children Aged 5-6 Years at TK IT Al-Azka, Jambi City.